(untitled) (Journal of the College of Education for Women, 2019)
The summary of this study is to identify the relation ship between exposuing of thepublic to foreign satellites and the degree of cultural of Iraqi public . the danger Iraqi publicexposure to foreign satellite specially some groups of the public are still own limited cultureand ideology without enough conscious to attitude of society . such people cun easily becontrolled by satellites , because these satellites may be the only cultural source for themwhich may badly affect their behaviour . This study also aims to identify the level of Iraqipeople exposure to foreign satellites and the types and motivations of that exposure , then torealize the relationship between exposing to foreign satellites and the cultural level of theIraqi public . This study is descriptive that aims to analyze a definite study which isstudying available facts or attitudes in addition of describing negate relationship to discoverthe facts related and generalize them .